PENGARUH GAYA KEPEMIMPINAN, KOMPETENSI, MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA APARATUR SIPIL NEGARA PADA KANTOR PENCARIAN DAN PERTOLONGAN MAKASSAR SULAWESI SELATAN - Rachman, Muhammad Fathur; Nasrullah, Nasrullah (COMPETITIVENESS, 2019)
This study aims to find out the picture of Leadership Style, Competence, Motivation, and Organizational Culture, to the Performance of State Civil Apparatus at the Makassar Search and Rescue Office of South Sulawesi This type of research is quantitative and located at the Makassar Search and Rescue Office of South Sulawesi. The population of this study, the entire ASN of 108 people. A sample of 52 people were drawn with simple random sampling techniques, data collected using surveys, questionnaire questionnaires, documentation.Data from the results of the study was analyzed with descriptive statistical analysis techniques and infrensial statistical analysis used is multiple linear regression. The results of this study showed that, (1) Leadership style has a significant positive effect on performance with P value = 0.028<0.05 with a coefficient value of 0.268 shows the more effective the leadership style is felt then the performance of employees in the Makassar Search and Rescue Office will increase. (2) Competency has a significant positive effect on performance with P value = 0.011< 0.05 with a coefficient value of 0.390 indicates that the better or more appropriate competencies that employees have with their work, thus encouraging the improvement of employee performance (3) Motivation has a significant positive influence on performance with P value=0.004< 0.0.05 with a coefficient value of 0.413, indicating that the better the employee's work motivation, the better the performance (4) The organizational culture has a significant positive influence on performance with P= 0.004<0.05 and a coefficient value of 0.458 which indicates that the better the organizational culture is felt then the employee performance will also increase. (5) Motivation has a dominant attitude towards ASN performance, because motivation variables are measured by four indicators, namely, basic needs, responsibilities, work environment, spiritual motivation. Keywords: Leadership Style, Competence, Motivation, Organizational Culture, and Performance.